Growth and production of beneng taro genotypes (Xanthosoma undipes K. Koch) on different soil organic carbon - Alghifari, Ahmad Fadli; Santosa, Edi; Susila, Anas Dinurrohman (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2023)
Beneng taro is a perennial of Araceae and becomes a new commodity in Indonesia. The research aimed to evaluate the growth and yield of beneng taro on various statuses of soil organic carbon (SOC). Three genotypes of taro, i.e., beneng Banten, beneng Bondowoso, and East Nusa Tenggara (NTT) fodder taro were planted in three SOC levels, i.e., 1.79, 2.94, and 4.09% in a randomized split block design in the Leuwikopo Experimental Station, IPB from April to December 2021. SOC was designed by adding cow manure. The results showed that there was no interaction between genotypes and SOC. The increase in SOC from 1.79 to 4.09% did not significantly affect growth but significantly affected the diameter and yield of beneng and NTT fodder taro. An increase in SOC above 1.79% markedly decreased tuber diameter, but conversely increased fresh tuber weight. Tuber weight increased by 5.6% and 12.1% with an increase in SOC from control to 2.94% and 4.09%, respectively. The increase in tuber weight was supported by the trend of increasing biomass weight and the number of roots. SOC source in the present study was cow manure which may also contribute some nutrients, therefore, further research is needed using neutral organic carbon sources to determine the effect solely. Keywords: Araceae; SOC; growth; manure; NTT taro; talas beneng Banten